Effectiveness Of Bioherbicide Kiambang (Salvinia molesta) on Growth of Gogo Rice (Oryza sativa L.) - Rizki Al Khairi Barus; Hapsoh Hapsoh; Wawan Wawan (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2023)
The main problem of upland rice cultivation is the presence of weeds, which cause a decrease in the quantity and quality of crop yields. Generally, farmers use synthetic herbicides to control weeds. One way to reduce the use of synthetic herbicides is by using kiambang extract bioherbicides which are applied to weeds. Currently, there is no research to determine the effect of kiambang extract on upland rice germination. The purpose of this study was to assess the effect of kiambang bioherbicide on the germination phase of upland rice by giving several concentrations of kiambang bioherbicide. This study used a completely randomized design (CRD) with 5 concentration treatments, namely 2,4-D herbicide, 20%, 40%, 60%, and 80% bioherbicide. Kiambang extract concentration was repeated 3 applicates for each replication; each experimental unit consisted of three Petri dishes containing 25 rice seeds. The research parameters were germination percentage, germination rate, length of the plumule, and radicle. Observational data were analyzed using analysis of variance (F test) at a level of 5% and continued with the Least Significance Different (LSD) test at a level of 5% to determine the difference between treatments. The results showed that the bioherbicide extract of kiambang (Salvinia molesta) 20% did not inhibit seed germination, but the seeds grew abnormally, while concentrations of 40%, 60%, and 80% inhibited germination.